Interleukin enhancer binding factor 2 (IEBF 2) was involved in the regulation of the antibacterial immune reactions in fresh water crayfish, Procambarus clarkii. (January 2022) - Yang, Bingbing; Lin, Sihan; Li, Bo; Wei, Zhe; Li, Qianqian; Shen, Xiuli; Du, Zhiqiang
Abstract: Although interleukin and interleukin analogues which play important immunomodulatory roles in mammals have not yet been reported in invertebrates, interleukin enhancer binding factor (IEBF) which acts as a transcription factor has been recently studied in several crustaceans and it may be involved in innate immune defence against pathogens. In this study, an IEBF 2 homologue was identified in the fresh water crayfish, Procambarus clarkii . The significantly changed expression levels of Pc - iebf 2 after bacterial challenge revealed the possibility of its participation in defence against bacterial infection. The results of an RNAi assay showed that the crayfish survival rate was obviously decreased after dsIEBF 2 injection, compared with the control groups. And S. aureus proliferation was obviously enhanced at 24 and 48 h post bacterial injection, when Pc - iebf 2 was knocked down. The possible molecular mechanisms for the innate immune regulation functions of Pc -IEBF 2 were also investigated. We speculated that Pc -IEBF 2 plays an important role in defending against bacterial infection in crayfish. It could regulate some innate immune responses by affecting the Toll signalling pathway, melanisation, and cell apoptosis. Highlights: Crayfish survival rate was decreased after Pc - iebf 2 was knocked down. Pc -IEBF 2 affected the production of AMPs and the trigger of melanisation. After Pc - iebf 2 was silenced, proapoptosis-associated genes were suppressed.